The Effect of Adding Semen Plasma & Some Types of Oils to the Semen Diluents of Awassi Rams on Vitality & Deformitied of Sperm Stored at 5°C for Different Periods (NTU Journal of Agriculture and Veterinary Science, 2022)
The current study was conducted to know the effect of adding seminal plasma and olive oil to diluted semen. Twelve Awassi rams were used, given a standard diet, and the diluted semen was divided into three groups; the first group was the control group, the second group was 3.5 ml of semen plasma / 100 ml of diluted semen while the third group had the addition of 3.5 ml of olive oil / 100 ml of diluted semen. Results obtained from this study indicate that there was a significant effect (P ? 0.05) increasing the percentage of individual motility and live sperm after 96 hours and in reducing the percentage of sperm abnormalities at 72 hours and sperm acrosomal abnormalities at 24 hours when adding semen plasma to sodium citrate diluent in. Futhermore, the addition of olive oil to dilute sodium citrate led to an increase in the percentage of live sperms at all preservation periods and to a decrease in the percentage of sperm and acrosome abnormalities. The storage periods of 48, 72 and 96 hours had a significant effect (P ? 0.05) on the studied traits, as the individual motility of the sperm and the live sperm were decreased with the increase of the preservation period. As for the percentage of sperm abnormalities and acrosome abnormalities of the sperm, it was increased with the progression shelf life at 96 hours compared to 24 hours.